Biometric study of Schizosphaerella, TOC, CaCO3 (Early Jurassic, Paris Basin) - Leonie Peti; Nicolas Thibault (PANGAEA, 2017)
Abundance and size changes in the calcareous nannofossil Schizosphaerella are investigated throughout the upper Sinemurian to lowermost Toarcian of the Sancerre-Couy core (Paris Basin). Measurements from 116 samples are compared to 487 and 411 measurements of CaCO3 content and total organic carbon (TOC) content, respectively. Our results confirm that Schizosphaerella was better adapted to proximal areas than coccoliths as expressed by the stepwise rise in abundance of Schizosphaerella, followed later on by the rise in abundance of coccoliths during the major transgression of the Sinemurian. The new results show that changes in the size of Schizosphaerella were mostly a response to Early Jurassic temperature variations (coldhouse-greenhouse changes). Large average sizes of Schizosphaerella correspond mostly to proximal, cool environmental conditions of the late Sinemurian. Medium average sizes correspond to more distal conditions and cool surface waters whereas small average sizes are associated with warm episodes. These results suggest that the size response of Schizosphaerella to the early Toarcian Oceanic Anoxic Event and to preceding environmental perturbations of the Early Jurassic was probably not a physiological response to lower calcification but rather represent changes in abundances of different ecophenotypes or (sub-) species related to climate change. The contribution of Schizosphaerella carbonate (CaCO3schizo) to the total carbonate (bulk CaCO3) in the Paris Basin was minor (<6 %) and short-term fluctuations of both parameters show no correlation. However, the CaCO3schizo and bulk CaCO3 show similarities in their long-term trends, suggesting a possible relationship between the biotic carbonate production and the export of allochthonous carbonate to the Paris Basin.
Supplement to: Peti, L; Thibault, N (2017): Abundance and size changes in the calcareous nannofossil Schizosphaerella – Relation to sea-level, the carbonate factory and palaeoenvironmental change from the Sinemurian to earliest Toarcian of the Paris Basin. Palaeogeography, Palaeoclimatology, Palaeoecology, 485, 271-282, https://doi.org/10.1016/j.palaeo.2017.06.019